Analisa Alternatif Perbaikan Untuk Mengatasi Drop Tegangan Pada Feeder Kota 20 KV Di Rokan Hulu - Muhammad Fadli Biya Lubis; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Power plant system is far away from central load. This resulted losses in the distribution ofelectrical power. The loss caused by the channel is long enough. So, in the distribution of electricalpower through the transmission and distribution electrical power, there are always drop voltagealong the transmission line. Large voltage drop that occurs greatly be affected by the large currentsand impedance values so that the voltage drop occurs in feeder city in Rokan Hulu and voltage dropthat occurs in feeder city of 17,581 kV or 12,095 % is still in PLN standard because it has notexceeded the standards determined that is equal to ±10% of nominal voltage There are several waysto correct voltage drop in the study are using the method of replacing the feeder cable, Capacitorbanks and tap-changing tranformer. From the analysis of the obtained that big’s voltage drop thatoccurs less than the prior improvements that are very instrumental in reducing a large voltage drop.In this repair the best lessening voltage drop is use capacitor bank of 18,900 kV or 8,015% ofvoltage about. And have met the PLN standard.Keyword : feeder cable, capacitor banks, tap-changing tranformer, voltage drop.